GSTT1, an increased risk factor for prostate cancer in patients with metabolic syndrome. Issue 4 (15th March 2022) - Liu, Dongdong; Che, Bangwei; Chen, Pan; He, Jun; Mu, Yi; Chen, Kehang; Zhang, Wenjun; Xu, Shenghan; Tang, Kaifa
Abstract: Background: Glutathione S‐transferase ( GST s) gene polymorphism and metabolic syndrome (Mets) are generally considered to be risk factors for prostate cancer (PCa). However, this conclusion is still controversial. There is a close relationship between GST s gene polymorphism and Mets. We suspect that the effect of GST s gene polymorphism and Mets on PCa may be the result of their joint action. As a result, the purpose of this study was to investigate the potential effect of GST s gene polymorphism on PCa in patients with Mets. Methods: We collected blood samples from 128 patients with PCa and 200 controls. The GST s gene polymorphism was detected by polymerase chain reaction‐restriction fragment length polymorphism (PCR–RFLP). Age, characteristics of Mets, frequencies of GST s gene polymorphism, total prostate volume (TPV), Gleason score, and prostate‐specific antigen (PSA) were recorded and analyzed. Results: There were significant differences in BMI, TG, LDL‐C, FBG, SBP, DBP, and HDL‐C among the control group, N‐PCa group, and Mets‐PCa group ( p < 0.05). GSTT1 null genotype (OR = 2.844, 95% CI: 1.791–4.517), GSTM1 null genotype (OR = 2.192, 95% CI: 1.395–3.446), and GSTP1 (A/G + G/G) genotype (OR = 2.315, 95% CI: 1.465–3.657) were associated with PCa susceptibility and malignancy. Only the GSTT1 null genotype in Mets patients was positively correlated with PCa. Conclusions: Our study suggests that GST s gene polymorphism may be a risk factor for PCa and can predict the susceptibility and malignancy of PCa. Secondly, in Mets patients, GSTT1 null genotype significantly increased the risk of PCa. GSTM1 null genotype and the effect of GSTP1 (AG + GG) on PCa were not significantly related to Mets. Abstract : After Mets was considered, GSTT1 null genotype was only significantly associated with PCa in Mets, and the risk of PCa occurrence increased by 7.867 times (95%CI: 3.073–20.141, p < 0.05), indicating that GSTT1 null genotype may be a significant predictor of PCa occurrence in Mets patients.